The Influence of Different Hand Tool Designs on the Perception of Aesthetics, Ergonomics and Usability - syed mohamed, muhammad syafiq (Centre for Promoting Ideas (CPI), USA., 2012)

(untitled)
The perception of products in terms of ergonomics, usability and beauty remains to be important issues in product design. A positive impression must be made for consumers. A product must be ergonomic and visually appealing in order for the product to be used safely and effectively. Therefore, understanding the perception of ergonomics, usability and aesthetics is an important issue for product designers. Apart from being visually appealing, the product must be perceived as ergonomic and usable, as the ergonomic design of hand tools may alleviate the occurence of upper limb musculoskeletal disorders. In this study, the perception of ergonomics, usability and aesthetics were evaluated for an existing hand tool (R1) and a proposed design (R2). Questions related to ergonomics, usability and aesthetics were combined to form a survey. A sample of 50 undergraduates were chosen as the respondents. The results indicated that R1 was rated less visually appealing than the new design, R2. Participants perceived the new design, R2 to be more ergonomic and usable than R1. Furthermore, a weak correlation between perception of ergonomics, usability and aesthetics were observed for this study. In general, ergonomic design factors are hard to be perceived by consumers. Possible ramifications of this relationship are discussed in this paper.